A description of the first zoeal stage of Pilumnus vinaceus A. Milne-Edwards, 1880 (Decapoda, Pilumnidae), with a revision of the first zoea morphology of Pilumnus Leach, 1815 - Douglas Fernandes Rodrigues Alves; João Alberto Farinelli Pantaleão; Rogério Caetano Costa; Fernando Luis Mantelatto (Papéis Avulsos de Zoologia, 2022)
Abstract The morphology of the first zoeal stage of Pilumnus vinaceus is described and compared with the zoea I of Pilumnus all species in the literature. Two ovigerous females of P. vinaceus were maintained in the aquarium facilities until the larvae hatch. The larvae of each ovigerous female were dissected using a stereoscopic microscope. The zoea I of P. vinaceus has common characteristics among the Pilumnidae as: [1] antenna of type 2; [2] maxilliped 1 with 2+2+3+3 setae on the basis and with 3,2,1,2,5 setae in the endopod; [3] maxilliped 2 with 1+1+1+1 setae on the basis and 1,1,6 setae on the endopod; [4] telson with furcal rami armed with dorsal and lateral spines. Considering the species of Pilumnus that occur in the western Atlantic, it becomes possible to identify P. vinaceus zoea I by means of the verification of the following characteristics: [1] pleonites with mediolateral processes; [2] number of setae on the antennule. It is however, important to consider that there is still a great deficit in the knowledge about the morphology of the larval forms of the species assigned to Pilumnus and we argue in favor of new descriptions to build a more robust dataset on zoeal morphology characters and use it in a phylogenetic context on the genus.